Theoretical-methodological aspects of landscape-hydrological structure of the territory research - Удовиченко, Вікторія Віталіївна (Київський національний університет імені Тараса Шевченка, 2016)
The basins of middle sized and small rivers, their tributaries have considerable levels of diversification, polystructural horizontal and vertical linkages. The complication of basins landscape structure parameterization noticeably increases needs to work out the theoretical-methodological and methodical aspects of their exploration and complex estimation. Taking into account such credence, the essence of landscape-hydrological analysis of the territory as one of the main methodical instrument of constructive-geographical researches is described in the article. The natural complex (geocomplex/landscape) of the rivers basin is defined as the key object of landscape-hydrological analysis and imagine as the area with definite state of water source where the process of water run-off formation takes place. The subject of research is mechanisms of forming and water displacement as the landscape component, or, by other words, hydrofunctioning. As the key tasks of landscape-hydrological analysis could be mention the hydrological features of natural complexes cognition, single out the landscape-hydrological systems (basins landscape systems) as an element of landscape and hydrological territory structure, landscape-hydrological mapping and distinguishing typological units analysis. The landscape-hydrological system (basin landscape system) is described as the part of earth surface where the interaction between hydrological processes and natural (landscapes) structures has local specificity that caused by one or several factors according to the spatial systems hierarchy. The conceptual basis of constructive-hydrological analysis of landscape structure of the territory directed to landscape planning tools implementation and landscape-planning actions elaboration at the regional and local levels is formed by the key geosystem approaches and principles, especially: zonal-azonal multiple-factor principle, basins principle, structural-hydrological, classification and mapping principles. The research process of landscape-hydrological structure of the territory includes a diversity of methodical procedures.

У представленій статті окреслено теоретико-методологічний апарат конструктивно-географічних ландшафтно-гідрологічних досліджень. Зокрема, знайшли своє відображення принципові аспекти сутності ландшафтно-гідрологічного аналізу території, його об’єктно-предметне поле, завдання та методичні настанови щодо реалізації. Стисло розкрито теоретико-методологічне підґрунтя формування ландшафтно-гідрологічних досліджень, а також базові геосистемні підходи та принципи, які формують концептуальну основу конструктивно-гідрологічних досліджень ландшафтної структури території, спрямованих на реалізацію інструментарію ландшафтного планування.
Теоретико-методологічні аспекти дослідження ландшафтно-гідрологічної структури території
Antipov А.N. I dr. Landshaftno-hydrologicheskije kharakteristiki Zapadnoj Sibiri / А.N. Antipov. – Irkutsk, 1989. – 221 s. Antipov А.N., Gagarinova О.V., Fedorov V.N. Landshaftnaja hydrologija: teorija, metodi, realizatzija / А.N. Antipov // Geographija i prirodnije resursi. – 2007. – №33. – S.56-67. Antipov А.N., Koritnij L.М. Geographicheskije aspekti gydrologicheskikh issledovanij / А.N. Antipov. – Novosibirsk, 1981. – 177 s. Antipov А.N., Fedorov V.N. Landshaftno-hydrologicheskaja organizatzija territorii. – Novosibirsk, 2000. – 254 s. Vernadskij V.I. Filosofskije misli naturalista / V.I. Vernadskij. – М., 1988. – 520 s. Vinogradov Ju.B. Matematicheskoje modelirovanije prozessov formirovanija stoka / Ju.B. Vinogradov. – L., 1988. – 365 s. Visozkij G.N. Izbrannije sochinenija: v 2-h tomakh / G.N. Visozkij. – М., 1957. – 314 s. Garzman I.N. Problemi geographicheskoj zonal’nosti i diskretnost’ gydrometeorologicheskikh polej v gornikh uslovijakh musonnogo klimata / I.N. Garzman // Tr. DVNIGMI, 1971. – Vip. 35. – S. 3-31. Gydrologicheskaja rol’ lesnikh geosystem / V.А. Snitko. – Novosibirsk, 1989. – 167 s. Glushkov V.G. Voprosi teorii i metodi gydrologicheskikh issledovanij / V.G. Glushkov. – М., 1961. – 416 s. Dokuchaev V.V. Pо voprosy оb osushenii bolot voobshe i v chastnosti pо osusheniju Poles’ja / V.V. Dokuchaev / Тr. Spb. оb-vа estestvoisp., 1875. – Т. 6. – S. 131-185. Ivanov К.Е. Gydrologija bolot / К.Е. Ivanov. – L., 1953. – 238 s. Koritnij L.М. Rechnoj bassejn kak geosystema / L.М. Koritnij // Dokl. Iн-tа geographii Sibiri i Dal’nego Vostoka. – – Vip. 42. – S. 33-38. Koritnij L.М. Bassejnovaja kontzeptzija v prirodopol’zovanii / L.М. Koritnij. – Irkutsk, 2001. – 161 s. Koritnij L.М., Bezrukov L.А. Vodnije resursi Angaro-Enisejskogo regiona (geosystemnij analiz) / L.М. Koritnij. – Novosibirsk, 1990. – 210 s. Kuchment L.S. Modeli protzessov formirovanija rechnogo stoka / L.S. Kuchment // Meteorologija i gydrologija, 1980. – №12. – S. 93-102. Molchanov А.А. Gydrologicheskaja rol’ lesa / А.А. Molchanov. – М., 1960. – 488 s. MuravejskijS.D.Rekiiozera. Gydrobiologija. Stok / S.D. Muravejskij. – М., 1960. – 388 s. Sosedov I.S. Metodika territorial’nikh vodnobalansovikh obobshenij v gorakh / I.S. Sosedov. – Аlmа-Аtа, 1976. – 150 s. Subbotin А.I., Zmieva Е.S., Nevegenko V.L., Мамаj I.I. Landshaftno-hydrologicheskij printzip izuchenija stoka / А.I. Subbotin // Landshaftnij sbornik. – М., 1973. – S. 175-189. HortonR.E. Erozionnojerazvitijerekivodosbornikhbassejnov / R.E. Horton. – М., 1948. – 158 s. Shvebs G.I. Teoreticheskije osnovi eroziovedenija / G.I. Shvebs. – Kiev-Odessa, 1981. – 223 s. Horton R. Erosional development of streams and their drainage basins; hydrological approach to quantitative morphology. – Bulletin of the Geological Society of America, Vol. 56, 1945. – 275-370. Scheidegger A.E. Horton’s Law of Stream Numbers. – Water Resources Research, Vol. 4, No.3, 1968. – P. 655-658. Strahler A. Quantitative analysis of watershed geomorphology. – Transactions of the AGU, 38, 1957. – P. 913-920.
Keywords: ландшафтно-гідрологічний аналіз; ландшафтно-гідрологічна система; ландшафтна структура; підхід; принцип; landscape-hydrological analysis; landscape-hydrological system; landscape structure; approach; principle